(untitled) (The Pretoria Student Law Review, 2021)
Climate change is becoming ever more pertinent and its impact ever more devastating. Issues such as deforestation, loss of biodiversity, and desertification are increasingly prevalent, leaving the present generation with numerous problems to contend with. But as climate change intensifies, those who will surely bear an even greater burden are the ones yet to come. Unless some form of equality is established between generations, future generations are likely to find themselves in a precarious and inhospitable environment. It is argued that one way of achieving an intergenerational balance is through a right to intergenerational equity. This article analyses the development and progression of the principle of intergenerational equity in international law. In doing so, the article interrogates the sources of international environmental law as well as international human rights law to determine whether a right to intergenerational equity exists. This analysis finds that no right to intergenerational equity has arisen under international law. Nonetheless, there seems to be a definitive trend toward the realisation of such a right on the international stage. Until such time as there is a right to intergenerational equity, certain institutions and mechanisms could be implemented or relied upon to safeguard the environmental interests of future generations.